MORFOLOGI, KLASIFIKASI, DAN SEBARAN CUMI-CUMI FAMILI LOLINGINIDAE - Diah Anggraini Wulandari (Pusat Penelitian Oseanografi LIPI, 2018)
MORPHOLOGY, CLASIFICATION, AND DISTRIBUTION OF SQUID FAMILY LOLINGINIDAE. Squids are one of Indonesian export commodities that is produced in frozen, salted, dried or canned, however the information about biology, ecology, habitat and distribution of squid are little known. Squid have ten tentacles equipped with suction, and generates ink to defend against their enemies. Squids are demersal or semi-pelagic animal that lives in the waters column up to a depth of 400 m with diurnal movements. Squids reproduce sexually and by deocious. Squids with family Lolinginidae (genus Lolious) are distributed across the Indonesian waters with temperatures of 8 to 32 C and salinity of 8.5 to 30 ppm. Familly Lolinginidae is grouped into several genera included Afrololigo, Allotheuthis, Dorytheuthis, Heterololigo, Loliolus, Lollinguncula, Pickfordiateuthis, Sepioteuthis, dan Urotheuthis